INTERSEKSI MASKULINITAS DAN AGAMA DALAM CERPEN ROBOHNYA SURAU KAMI KARYA A. A. NAVIS - Hidayatullah, Danial (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
This research aims to find out how gender and narrative correlate to each other. Traditionally speaking, gender is only related to one of the intrinsic aspects, the character, which is usually inside the plot. Although in this short story the narrator is character-bound narrator, the narrator is not in the fabula or plot. The implication is that it can be assumed that gender plays its role. The narrator in this short story obviously gets involved in the contestation of masculinity of the characters. The method of narratology is employed to dig out all of the masculine contestation, among the main characters (Ajo Sidi and Sang Kakek/the Oldman) and the narrator. The result shows that the masculinity of Ajo Sidi belongs to the hegemonic masculinity and the masculinity of the Oldman belongs to the non-hegemonic masculinity. The contestation of masculinity represents the binary opposition between active and passive masculinity. In this respect, the masculinity of the Oldman, which is passive, can be binarized as the feminine rather than masculine one.